Factors affecting classroom participation and how participation leads to a better learning. (2nd January 2019) - Precourt, Elena; Gainor, Maryella
ABSTRACT: The purpose of this paper is twofold. First, we analyze various course- and student-related factors that affect participation grades within several college accounting classes. The second purpose is to determine whether in-class participation grades have an effect on exam performance in these classes. We find that, unlike in liberal arts and sciences courses, in accounting courses, participation grades for female students do not differ from participation grades for their male counterparts, regardless of class level. Overall, course level and student major have no direct effect on participation grades; however, the accounting majors and students in the lower level courses have better attendance than do non-accounting majors and students in more advanced courses. We observe that class schedule, in particular class duration and semester, affects students' participation performance. Lastly, we find that students who participate more in classroom discussions perform 25% better on exams than do those with lower participation grades. This relationship holds for the three elements of participation grading: frequency of participation, consistency of participation, and attendance.